Liceu de Artes e Ofícios do Rio de Janeiro, dos pressupostos aos reflexos de sua criação: de 1856 a 1900 - Bielinski, Alba Carneiro (2003)
Concerned with the creation of the "Liceu de Artes e Oficios do Rio de Janeiro" (School of Arts and Crafts of Rio de Janeiro) on 23 November 1856 and studies it’s trajectory untill the end of the XIXth Century. A detailed research of the primary sources and the analysis of the speeches of the conceiver of the "Liceu", Béthencourt da Silva, served as a starting point to the comprehension of the fact that this institution fullfilled the lacks of the sector of the formation of qualified workers, giving response to the need of popular and technical education for the industry. This question had not yet been solved and had already been the object of the initial proposal of the "Missão Artistica Francesa" (1816) and of the "Reforma Pedreira" (1855) to the Academia de Belas Artes (Fine Arts Academy). This work not only presents a deep reflection about the dichotomy betweem fine arts and crafts in Brazil in the XIXth Century, but also organizes the information about the "Liceu" that was, hitherto, dispersed in archives and libraries, thus making easier the future researches about the subject. The approach of this inedited theme constitutes a contribution to the literature regarding the professional-technical sector and the artistic education in Brazil.